2021
DOI: 10.1073/pnas.2024258118
|View full text |Cite
|
Sign up to set email alerts
|

DDX11 loss causes replication stress and pharmacologically exploitable DNA repair defects

Abstract: DDX11 encodes an iron–sulfur cluster DNA helicase required for development, mutated, and overexpressed in cancers. Here, we show that loss of DDX11 causes replication stress and sensitizes cancer cells to DNA damaging agents, including poly ADP ribose polymerase (PARP) inhibitors and platinum drugs. We find that DDX11 helicase activity prevents chemotherapy drug hypersensitivity and accumulation of DNA damage. Mechanistically, DDX11 acts downstream of 53BP1 to mediate homology-directed repair and RAD51 focus f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Here we started out by investigating the functions of CTF18-RFC versus DDX11, both associated with DNA repair and implicated in human disease ( Gellon et al 2011 ; Price et al 2013 ; Abe et al 2018b ; van Schie et al 2020 ; Jegadesan and Branzei 2021 ). We found that in avian DT40 cells, CTF18 loss causes negligible defects, but combined deficiency in CTF18 and DDX11 genes causes synthetic lethality due to severely compromised SCC and chromosome missegregation.…”
Section: Discussionmentioning
confidence: 99%
“…Here we started out by investigating the functions of CTF18-RFC versus DDX11, both associated with DNA repair and implicated in human disease ( Gellon et al 2011 ; Price et al 2013 ; Abe et al 2018b ; van Schie et al 2020 ; Jegadesan and Branzei 2021 ). We found that in avian DT40 cells, CTF18 loss causes negligible defects, but combined deficiency in CTF18 and DDX11 genes causes synthetic lethality due to severely compromised SCC and chromosome missegregation.…”
Section: Discussionmentioning
confidence: 99%
“…Chl1/DDX11 —Mutations in DDX11 underlie the cohesinopathy Warsaw breakage syndrome [ 132 , 133 ]. DDX11 deficiency sensitizes to various types of DNA damage including PARP-inhibition, G4-stabilization, UV, cisplatin, ATR inhibition, and Topoisomerase inhibition [ 84 , 110 , 134 , 135 ]. DDX11 facilitates DNA replication, fork restart, and the processing of G4 structures [ 84 , 125 , 130 ].…”
Section: Sister Dna Entrapment At Processive Replication Forksmentioning
confidence: 99%
“…DDX11 facilitates DNA replication, fork restart, and the processing of G4 structures [ 84 , 125 , 130 ]. In response to DNA damage, Chl1/DDX11 promotes the formation of ssDNA as a suitable substrate for RPA loading, thereby contributing to efficient CHK1 activation, RAD51-dependent HR, and cohesin loading on stalled replication forks [ 58 , 85 , 135 ]. All functions of Chl1/DDX11 in DNA replication and repair depend on its helicase function [ 58 , 82 , 84 , 135 ].…”
Section: Sister Dna Entrapment At Processive Replication Forksmentioning
confidence: 99%
See 2 more Smart Citations